TECHNOLOGICAL ADVANCEMENTS AND THEIR ROLE IN WORK STRESSORS AND WORK-LIFE BALANCE: A CONCEPTUAL FRAMEWORK FOR THE DIGITAL AGE - Masri, Hanis Marhaini; Rakiman, Umol Syamsyul (INTERNATIONAL JOURNAL OF ENTREPRENEURSHIP AND MANAGEMENT PRACTISES (IJEMP), 2025)
Technology’s quick development has fundamentally altered the nature of work, offering both benefits and challenges in managing workplace pressures and striking a balance between work and home life. With an emphasis on how digital tools and platforms affect the lines between work and home life, this conceptual paper investigates the connection between technological developments and their effects on job-related pressures. This study examines how technology can be both an efficiency enhancer and a possible cause of stress, drawing on important theoretical frameworks such as the Boundary Theory and the Job Demands-Resources (JD-R) model. Employees can now be contacted at any time because to the enhanced connectedness brought about by technology tools like smartphones, email, and cloud-based communication systems. But the continual connectedness has made it harder to distinguish between work and personal life, which leads to more stress at work. Additionally, although technology might increase flexibility, it frequently leads to a culture that is "always-on," which exacerbates burnout and makes it difficult to completely disconnect from work. This paper makes the case that although technology has enormous potential to increase productivity and flexibility at work, its widespread impact on work-life balance calls for a reassessment of both organizational and personal coping strategies. This paper proposes a conceptual framework to understand the impact of technology, emphasizing the need for adaptive work practices, digital detox strategies, and organizational policies that prioritize employee well-being. By providing insights into how businesses and individuals might handle the challenges of the digital age, the study hopes to add to the expanding corpus of literature on digital work-life integration and stress management. In an increasingly interconnected world, the paradigm offers a starting point for future study that may direct interventions meant to lessen work-related stress and improve work-life balance.